Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.